Comparitive advertising - Vanessa Bloom (Communicare)
At a meeting of the Association of Advertising Agencies In 1989, members voted against comparative advertising, but the mere fact that the AAA found the Issue Important enough to bring to a ballot and because the outcome was so close, proves just how relevant and Immediate this issue is. This exploratory Informal article aims to "stir the pot" and generate debate on this controversial practice. The lack of unanimity amongst practitioners in the Industry and the findings of the Informal pilot study point to a need for substan tial consumer research, something which to date has been sorely neglected. This article does not profess to do anything more than suggest hypotheses for study, but is does prove that the Issue of comparative advertising should not be "swept under the carpet" by a conspiracy of reluctance to "upset the apple-cart", but should be looked at honestly, from both the Industry's and the consumers' point of view.